PENGGUNAAN INSTRUMEN TES UNJUK KERJA PADA PEMBELAJARAN SENI TARI DI SMK NASIONAL 2x11 KAYUTANAM - Dewi Fiolinda; Indrayuda Indrayuda; Yos Sudarman (FBS Universitas Negeri Padang, 2018)
AbstractThis article aims to find out and describe the use of the instrument test performance on learning the art of dance in the CMS National 2x11 Kayutanam. The method used is descriptive qualitative approach method of analysis. The object of research is the teacher of art and culture (dance) National 2x11 ayutanam CMS. Research instrument is the interview guidelines, notes the observation and study of the literature. The data analysis techniques is collecting data, data presentation, data meredaksi and verify the data. Findings from the research tells us that the use of the test instrument performance in National 2x11 SMK kayutanam already applied by the teachers of art and culture as well. So the use of a performance test instrument made in the RPP can be maintained by the teacher to assess and measure the ability of their students in learning. Keyword: Performance Test Instruments, learning the art of Dance